Video Review of Baseline Performance on Global Ratings in a Double‐Blind Placebo Surgery Trial. Issue 6 (4th October 2018) - McRae, Cynthia; Caspari, Jennifer; Russell, Daniel; Ellgring, Heiner; Bezzant, Chris; Greene, Paul; Fahn, Stanley
Abstract: Background: A randomized controlled double‐blind sham surgery trial was conducted to determine the effectiveness of implantation of human embryonic dopamine neurons into the putamen of patients with advanced Parkinson's disease (PD). The present analyses determined whether patients viewing a video of them performing motor activities off medications at baseline would affect self‐ratings 12 months later on the Global Rating Scale (GRS). Objectives: To examine changes in GRS scores pre‐ and post‐video review for the total sample; to examine differences in scores between actual implant and sham groups, as well as perceived groups pre‐ and post‐video review; to examine differences among four subgroups of patients based on actual and perceived treatment (i.e., actual implant/perceived implant). Methods: Forty participants were recruited and randomly assigned to receive either neural implantation or sham surgery. The primary outcome variable was a one‐item GRS ranging from −3 (much worse since surgery) to +3 (much improved since surgery). At 12 months (before the blind was lifted) patients rated themselves on the GRS before and after viewing the baseline video. Results: Total sample GRS scores improved after the video ( P = .001). There were no differences between the actual implant and sham groups before or after the video, but there were differences between perceived groups at both times ( P < .001). Among subgroups, improvement after the video was found only in the group receiving the implant but who thought sham ( P = .011). Conclusions: When self‐ratings are an outcome variable, review of baseline videos is recommended before making comparative ratings.